26 მაისი მეხსიერების პოლიტიკის კონტექსტში (1921-1922) - Matsaberidze, Malkhaz (Politics / პოლიტიკა; 2018: მეოთხე ნომერი, 2019)
The 26th of May in the Context of the Memory Politics (1921-1922) The Soviet regime, imposed on Georgia in February-March, 1921, after its occupation by the Russian Red Army, claimed that it would defend the sovereignty of Georgia, thus it was forced to celebrate the 26 of May in 1921; although the new government tried to attach the “Soviet Content” to it through claiming that after the Sovietization the true freedom was gained by the workers of Georgia. Although, this was a dangerous move, as the May 26 represented the symbol of the independent statehood of Georgia; thus, it was immediately abandoned by the communist regime. From 1922, the Soviet Rule prohibited the celebration of the May 26 and it was substituted by the February 25 – the day of entrance of the Russian Red Army in Tbilisi, which was declared as the day of the “Soviet Georgia.”
Keywords: 26 May, Georgia